Intelligent security algorithm for UNICODE data privacy and security in IOT - Maram, Balajee; Gnanasekar, J. M.; Manogaran, Gunasekaran; Balaanand, M. (Service oriented computing and applications, 2019)
Information security algorithms provide praxis for security to the different forms of data. Data are transmitted in different forms like ASCII text, UNICODE text, audio, video, image, etc. Different algorithms have been proposed by various researchers for handling text security. The existing cryptographic algorithms are working on ASCII text. Multilingual data communication is so prevalent in the digital era. In the digital era, many symmetric cryptographic algorithms have been introduced using S-boxes. S-box is a vital component for some cluster of cryptographic algorithms. Some cryptographic algorithms depend on the static S-box, which yields insecurity to the digital data. The existing S-box concept handles ASCII text only. This research paper presents the Substitution box (S-box) that is dynamic and key-dependent. Dynamic and key-dependent S-box wraps the data with high security. This S-box works with UNICODE text which includes UTF-16. It was tested for UNICODE text using python language. It concludes that the novel S-box is suitable for handling UNICODE text and shows better performance.